2003
DOI: 10.1021/ja028337j
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Synthesis of Charged Copper and Silver Fischer Carbenes from Diazomalonates:  Mechanistic and Conformational Considerations in Metal-Mediated Wolff Rearrangements

Abstract: J. Am. Chem. Soc. 2003, 125(15), 4478-4486. IntroductionThe gas phase synthesis of metallo-carbenoid compounds has a surprisingly long history. 1 In early studies, the metallo-carbenoids were created by high energy methods utilizing electron impact ionization. The resulting ions were then used in bimolecular reactions with various neutral molecules to study the chemistry of and determine metalcarbon bond strengths for these charged Fischer carbenes. The importance of studying gas phase species in determining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 26 publications
1
46
0
Order By: Relevance
“…In a combined mass spectrometry and computational study, Beauchamp and Stoltz have demonstrated the formation and rearrangement of a silver carbene species derived from dimethyl diazomalonate. 9 In this study, the first stable species observed was the b-diketo complex 2 (for comparison see complex 21 in Fig. 8.2), which, on activation using low-energy collision-activated dissociation (CAD), loses the acetonitrile ligand, producing 3 (Scheme 8.1).…”
Section: Wolff Rearrangementmentioning
confidence: 77%
See 1 more Smart Citation
“…In a combined mass spectrometry and computational study, Beauchamp and Stoltz have demonstrated the formation and rearrangement of a silver carbene species derived from dimethyl diazomalonate. 9 In this study, the first stable species observed was the b-diketo complex 2 (for comparison see complex 21 in Fig. 8.2), which, on activation using low-energy collision-activated dissociation (CAD), loses the acetonitrile ligand, producing 3 (Scheme 8.1).…”
Section: Wolff Rearrangementmentioning
confidence: 77%
“…Additional support for this decomposition pathway was provided through the use of labeled substrates (deuterium or 13 C), although these experiments were performed with the corresponding copper system, which underwent similar chemistry. 9 Chavan and coworkers provide evidence that the Wolff rearrangement is facilitated by the formation of silver nanoclusters, which initiate electron transfer to the diazo compound providing 8. While the precise fate of this species remains to be firmly established, they suggest a multicycle process involving the intermediacy of a silver carbene 10 (Scheme 8.2).…”
Section: Wolff Rearrangementmentioning
confidence: 99%
“…124 However, if the diazo compound is derived from malonate, having an additional ester functional group, the products formed will be an olefin 125 126 or a Fischer carbene 127 if copper(I) or silver(I) are present whereas divalent metals do not promote the carbene formation (Scheme 34). 126 The vacuum pyrolysis 127 or matrix photolysis 128 of cyclic diazo compounds was observed to provide the decarbonylated product after ring contraction reaction.…”
Section: Decarbonylationmentioning
confidence: 99%
“…Thus, isolated ions are available for structural analysis by tandem mass spectrometry using techniques such as CID, providing information about organometallic complex stoichiometries. Table 2.1 lists some of the mechanistic studies of organic and organometallic reactions reported in the literature by ESI-MS. All sorts of reactions have been successfully explored in the gas phase, such as the Baylis-Hillman reaction [211][212][213], C-H or N-H activation [214][215][216][217][218][219], cyclopropanation reaction [220], Diels-Alder reactions [221], displacement reactions [222], electrophilic fluorination [223,224], Fischer indole synthesis [225], Gilman reaction [226,227], Grubbs metathesis reaction [228][229][230][231], Heck reaction [194], methylenation [232], oxidation [233,234], Petasis olefination reaction [235], Raney Nickel-catalyzed coupling [236], ruthenium (II)-catalyzed asymmetric reduction [237], Stille reaction [238], sulfoxidation [239], Suzuki reaction [240], Wittig reaction [241], Wolff rearrangement [242], Ziegler-Natta olefin oligomerization [243], Pd-catalyzed CÀC bond formation [244][245][246][247][248]...…”
Section: Mechanism Elucidation Of Organometallic Reactionsmentioning
confidence: 99%